2012
DOI: 10.1016/j.bbi.2011.12.007
|View full text |Cite
|
Sign up to set email alerts
|

Serum sTNF-R1, IL-6, and the development of fatigue in patients with gastrointestinal cancer undergoing chemoradiation therapy

Abstract: Although evidence of inflammation and fatigue has been noted in cancer survivors, whether inflammation is linked to the expression of fatigue and other symptoms arising from concurrent chemoradiation therapy (CXRT) has not been well studied. Patients undergoing CXRT for locally advanced colorectal or esophageal cancer (n = 103) reported multiple symptoms weekly via the M. D. Anderson Symptom Inventory (MDASI) from start of therapy. Serum samples were collected weekly to examine changes in inflammatory markers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
84
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 99 publications
(90 citation statements)
references
References 29 publications
5
84
0
1
Order By: Relevance
“…In an interventional study of patients undergoing curative CRC resection, Malicki and co-workers found a significant reduction in pre-operative serum IL-6 in patients receiving statins (96). In contrast however, a recent study of the systemic inflammatory response to neoadjuvant chemoradiotherapy in patients with oesophageal and rectal cancer found that concomitant statin use did not attenuate the serum inflammatory response or treatment-associated symptoms (97). Further clarification of the effects of statins on cancer-related systemic inflammation is required, and such measures should be incorporated in to future studies of the chemotherapeutic benefits of statins.…”
Section: Systemic Inflammationmentioning
confidence: 88%
“…In an interventional study of patients undergoing curative CRC resection, Malicki and co-workers found a significant reduction in pre-operative serum IL-6 in patients receiving statins (96). In contrast however, a recent study of the systemic inflammatory response to neoadjuvant chemoradiotherapy in patients with oesophageal and rectal cancer found that concomitant statin use did not attenuate the serum inflammatory response or treatment-associated symptoms (97). Further clarification of the effects of statins on cancer-related systemic inflammation is required, and such measures should be incorporated in to future studies of the chemotherapeutic benefits of statins.…”
Section: Systemic Inflammationmentioning
confidence: 88%
“…Most of the enrolled patients (Table 2) in the study were receiving cancer therapy. As CRF varies according to the cycle and duration of cancer therapy (ie, chemotherapy or targeted therapy or radiation therapy), 67,68 the cancer therapy can be a confounder in this study. Also because this study had no placebo arm, the efficacy of PG may have been due to a placebo effect.…”
Section: Discussionmentioning
confidence: 99%
“…The pro-inflammatory cytokine, IL-4, was associated with the constellation of fatigue, pain, sleep disturbance, and depression symptoms in cancer survivors [41]. Overexpression of pro-inflammatory cytokines, sTNF-R1 and sIL-6, was associated with fatigue development over the course of chemoradiation treatment for gastrointestinal cancer [42]. To better understand the mechanisms underlying self-reported CRF, future research can include biological data such as inflammation markers.…”
Section: Fatigue Variationsmentioning
confidence: 98%